2021
DOI: 10.1177/21514593211020700
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Obesity With Low Muscle Mass and Physical Function in Patients With End-Stage Knee Osteoarthritis

Abstract: Objective: To investigate the prevalence of obesity with low muscle mass and its impact on physical function, quality of life (QOL) and pain in patients with end-stage knee osteoarthritis over 65 years old. Methods: In this cross-sectional study, we assessed a total of 562 patients. After separating the group into males and females, we divided patients into 4 further groups: normal BMI with normal muscle mass, obesity with normal muscle mass, normal BMI with low muscle mass and obesity with low muscle mass. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“… 27 - 29 The combination of sarcopenia and obesity (i.e., sarcopenic obesity) is associated with impaired physical function and quality of life in patients with advanced knee OA. 30 Nonetheless, this shows compelling evidence that sarcopenia and/or obesity is present in knee OA but poorly recognized/not recognized at all as sarcopenic obesity. This is very important to consider while assessing one of the abovementioned disorders.…”
Section: Discussionmentioning
confidence: 89%
“… 27 - 29 The combination of sarcopenia and obesity (i.e., sarcopenic obesity) is associated with impaired physical function and quality of life in patients with advanced knee OA. 30 Nonetheless, this shows compelling evidence that sarcopenia and/or obesity is present in knee OA but poorly recognized/not recognized at all as sarcopenic obesity. This is very important to consider while assessing one of the abovementioned disorders.…”
Section: Discussionmentioning
confidence: 89%
“…The longitudinal study by Kim and colleagues [ 32 ] found that an increase in visceral fat mass resulted in a decrease in skeletal muscle mass, which demonstrates the synergistic action of the two clinical entities, sarcopenia and obesity. Thus, sarcopenic obesity may have a greater effect on metabolic disorders; cardiovascular disease; increased risk of osteopenia, osteoporosis, fractures and falls; and mortality than either sarcopenia or obesity separately [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Low muscle mass as well as high body fat become evident with disease progression of KOA [24,90], sarcopenic obesity becomes prevalent at late stage of KOA. The overall sarcopenic obesity prevalence at end-stage KOA has been estimated to be 2.7−17.2% for the elder population in Asia [26,31,91] and 2.6−9.4% in other areas worldwide [27,32], regardless of sex, age, and identification criteria of sarcopenic obesity. In this study cohort, 59 out of 587 (10.1%) patients with moderate or severe KOA were classified as having sarcopenic obesity, which agrees with previous results.…”
Section: Prevalence Of Sarcopenic Obesity and Nutritional Status In End-stage Knee Osteoarthritismentioning
confidence: 99%
“…In addition to obesity, low muscle mass (i.e., sarcopenia) has been given as a risk factor for KOA and its disease progression [22][23][24]. Notably, the obese older individuals with KOA who are classified as having sarcopenia (i.e., sarcopenic obesity) may suffer potential risks of physical decline and disability [25][26][27]. Sarcopenic obesity is a condition referring to the coexistence of sarcopenia and obesity and threatens physical health in elderly populations [28], with an overall global prevalence of 11% in older adults [29].…”
Section: Introductionmentioning
confidence: 99%